2019
DOI: 10.5194/isprs-archives-xlii-2-w15-609-2019
|View full text |Cite
|
Sign up to set email alerts
|

Digital Twin: A Hbim-Based Methodology to Support Preventive Conservation of Historic Assets Through Heritage Significance Awareness

Abstract: <p><strong>Abstract.</strong> During preliminary phases of conservation projects, a considerable amount of heterogeneous datasets are produced, gathered, analysed and interpreted. Abundant researches have gradually proven that Historic Building Information Modelling (HBIM) is a relevant alternative for the collaborative management of information related to existing structures. Apart from the obvious benefits of HBIM for information exchange among stakeholders during conservation project, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 17 publications
0
48
0
6
Order By: Relevance
“…This phenomenon can be illustrated by the significant amount of research focussing on the development of the third dimension in Geographic Information System (GIS) and Computer-Aided Design (CAD) environments. At the same time, researchers in the field of Cultural Heritage have progressively considered Building Information Model/Modelling/Management (BIM) and its interoperable exchange format (Industry Foundation Classes (IFC)) as a relevant alternative for the management of information [14] related to immovable heritage. Rather than being in conflict, BIM and GIS can be considered to be complementary [42], because they deal with different issues and scales, and even though no existing commercial software has yet proposed a fully integrated BIM-GIS solution, the current state of the research seems to indicate the progressive merging of both.…”
Section: Heritage Information Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…This phenomenon can be illustrated by the significant amount of research focussing on the development of the third dimension in Geographic Information System (GIS) and Computer-Aided Design (CAD) environments. At the same time, researchers in the field of Cultural Heritage have progressively considered Building Information Model/Modelling/Management (BIM) and its interoperable exchange format (Industry Foundation Classes (IFC)) as a relevant alternative for the management of information [14] related to immovable heritage. Rather than being in conflict, BIM and GIS can be considered to be complementary [42], because they deal with different issues and scales, and even though no existing commercial software has yet proposed a fully integrated BIM-GIS solution, the current state of the research seems to indicate the progressive merging of both.…”
Section: Heritage Information Systemmentioning
confidence: 99%
“…This method makes it possible to capture the entire complexity of heritage information with all the interplay and relationships between the different data and enables stakeholders to extract key information by performing complex queries. Additionally, it has been suggested that the Internet of Things appears to be the next important challenge as it spreads within the construction sector [40], and it has been proposed to take advantage of these infrastructures to support preventive conservation of immovable heritage [14,51]. Considering the previous considerations and V. Heras' recommendation to focus future research on "how these technologies (ICT tools in heritage conservation) can improve and support heritage planning and management", the concept of the Digital Twin and its possible applications in the field of Cultural Heritage will be discussed in the next section.…”
Section: Hbimmentioning
confidence: 99%
See 3 more Smart Citations